PENGARUH TERAPI TARI TERHADAP PENURUNAN TINGKAT STRES PADA ANAK - Fitriatul Masruroh; Rizki Wiji Nugroho (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2021)
The study aims to test the influence of dance therapy with reduced stress levels. The subjects in this study were students of SMAN 1 BANGIL. The sample count in this study was 30 male and female students, taken with Purposive Random Sampling technique. Statistical analysis used for hypothesis testing is a correlation of t-test and replay. The results of the analysis obtained F = 13,122, R = 0.213 with p = 0.001 (p<0.01) means there is a very significant influence between dance therapy and decreased stress levels in adolescents. The analysis result between A1 – A2 obtained t = 3,622 with p = 0.001 (p<0.01), average A1 = 62,267 and average A2 = 45,633 which means A1 > A2. This shows there is a very significant difference between before being given dance therapy (pre-test) and after being given dance therapy (post-test) where the level of stress in adolescents decreases after being given dance therapy.